Plasmodium falciparum Is Able To Invade Erythrocytes through a Trypsin-Resistant Pathway Independent of Glycophorin B - Gaur, Deepak (Infect Immun, 2003)
Plasmodium falciparum invades erythrocytes through multiple ligand-receptor interactions, with redundancies in each pathway. One such alternate pathway is the trypsin-resistant pathway that enables P. falciparum to invade trypsin-treated erythrocytes. Previous studies have shown that this trypsin-resistant pathway is dependent on glycophorin B, as P. falciparum strains invade trypsin-digested glycophorin B-deficient erythrocytes at a highly reduced efficiency. Furthermore, in a recent study, the P. falciparum 7G8 strain did not invade glycophorin B-deficient erythrocytes, a finding that was not confirmed in the present study. To analyze the degree of dependence on glycophorin B for invasion by P. falciparum through the trypsin-resistant pathway, we have studied the invasion phenotypes of five parasite strains, 3D7, HB3, Dd2, 7G8, and Indochina I, on trypsin-treated normal and glycophorin B-deficient erythrocytes. Invasion was variably reduced in glycophorin B-deficient erythrocytes. Four strains, 3D7, HB3, Dd2, and Indochina I, invaded trypsin-treated erythrocytes, while invasion by the 7G8 strain was reduced by 90%. Among the four strains, invasion by 3D7, HB3, and Dd2 of trypsin-digested glycophorin B-deficient erythrocytes was further reduced. However, Indochina I invaded trypsin-digested glycophorin B-deficient erythrocytes at the same efficiency as its invasion of trypsin-digested normal erythrocytes. This strongly suggests that the Indochina I strain of P. falciparum is not dependent on glycophorin B to invade through a trypsin-resistant pathway as are the strains 3D7, HB3, and Dd2. Thus, P. falciparum is able to invade erythrocytes through a glycophorin B-independent, trypsin-resistant pathway.